Owners’ integrity, customers’ relation, and focused attitude as strategiies of family business sustainability and growth: an empirical study - John Tampil Purba; Jacob Donald Tan (Universitas Hayam Wuruk Perbanas, 2018)
Asian Development Bank Institute reported that the contribution of Micro, Small and Medium Enterprises (MSMEs) to the Indonesian GDP is 57.8% and the contribution to total employment is 97.2%. MSMEs in Indonesia are almost owned by families. According to Family Firm Institute in 2016, 72% of all businesses in Indonesia’s private sector are run by family businesses, and while most of the MSMEs started out as family businesses, many successful entrepreneurs come from family business background. This empirical study is based on 3 family business cases that have been expanding in terms of its sales and operations throughout more than 10 years. The method used in this study is qualitative research by exploring the strategic management to sustain the family businesses through owners’ integrity, customers’ relations, and focused attitude in their vocations. As the family businesses are currently in transition of passing the torch to the next generation, their sustaining strategies have to be extended.